2022
DOI: 10.3390/ijms231810217
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Component Analyses in Different Varieties of Actinidia eriantha Kiwifruit by Transcriptomic and Metabolomic Approaches

Abstract: Actinidia eriantha is a unique germplasm resource for kiwifruit breeding. Genetic diversity and nutrient content need to be evaluated prior to breeding. In this study, we looked at the metabolites of three elite A. eriantha varieties (MM-11, MM-13 and MM-16) selected from natural individuals by using a UPLC-MS/MS-based metabolomics approach and transcriptome, with a total of 417 metabolites identified. The biosynthesis and metabolism of phenolic acid, flavonoids, sugars, organic acid and AsA in A. eriantha fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…49,50 Similarly, a recent study on three A. eriantha genotypes indicated that the expression of a kiwifruit gene, MDH1, exhibited a significant positive correlation with the content of malic acid. 43 However, although the expression level of AePEPC2 was positively correlated with PEPC activity during fruit development, the correlation value was not significant (Fig. 6).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…49,50 Similarly, a recent study on three A. eriantha genotypes indicated that the expression of a kiwifruit gene, MDH1, exhibited a significant positive correlation with the content of malic acid. 43 However, although the expression level of AePEPC2 was positively correlated with PEPC activity during fruit development, the correlation value was not significant (Fig. 6).…”
Section: Discussionmentioning
confidence: 89%
“…In fruit of another kiwifruit cultivar, A. eriantha ‘Ganmi 6’, the predominant organic acid are quinic acid and citric acid, accounting for 62.68–83.21% of the total organic acids during different developmental periods 26 . For other three varieties of A. eriantha , the main organic acids in fruit are citric acid, succinic acid and d ‐xylonic acid 43 . Therefore, for kiwifruit, the accumulation patterns, types, and contents of organic acids in fruit probably exhibit obviously different features, mainly depending on the species or varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…deliciosa, A. eriantha, and A. arguta) have been developed as commercial cultivars so far. Due to its nutrient and commercial values, extensive investigations on genomics (Huang et al 2013;Pilkington et al 2018;Tang et al 2019;Wu et al 2019;Yue et al 2023), transcriptomics (Choi et al 2022;Tahir et al 2022;Miao et al 2023;Xiong et al 2023), and metabolomics (Abid et al 2022;Jia et al 2022;Wang et al 2022a;Wang et al 2022c;Shu et al 2023;Zhang et al 2023) of kiwifruit have been carried out. However, functional genomic studies (Akagi et al 2019;Peng et al 2019;Fu et al 2021;Varkonyi-Gasic et al 2021;Wang et al 2022) are limited, partially because the genetic modification of kiwifruit is difficult and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…A. eriantha ‘White’, A. eriantha ‘Shanong 18’, and A. eriantha ‘Ganmi 6’ are the dominant A. eriantha , and only one hybridized cultivar, A. eriantha ‘Jinyan’, has been registered. A. eriantha fruits are rich in Vc, minerals, and a variety of amino acids, with unique flavours [ 37 ]. Therefore, the synthesis and accumulation of vitamins, sugars, and organic acids during the growth and development process play a crucial role in the fruit quality and its unique flavour.…”
Section: Introductionmentioning
confidence: 99%